Impact of a Realistic Density Stratification on a Simple Solar Dynamo Calculation - Lopes, I (2012)
In our Sun, the magnetic cycle is driven by the dynamo action occurring inside the convection zone, beneath the surface. Rotation couples with plasma turbulent motions to produce organized magnetic fields that erupt at the surface and undergo relatively regular cycles of polarity reversal. Among others, the axisymmetric dynamo models have been proved to be a quite useful tool to understand the dynamical processes responsible for the evolution of the solar magnetic cycle and the formation of the sunspots. Here, we discuss the role played by the radial density stratification on the critical layers of the Sun on the solar dynamo. The current view is that a polytropic description of the density stratification from beneath the tachocline region up to the Sun's surface is sufficient for the current precision of axisymmetric dynamo models. In this work, by using an up-to-date density profile obtained from a standard solar model, which is itself consistent with helioseismic data, we show that the detailed peculiarities of the density in critical regions of the Sun's interior, such as the tachocline, the base of the convection zone, the layers of partial ionization of hydrogen and helium, and the super-adiabatic layer, play a non-negligible role on the evolution of the solar magnetic cycle. Furthermore, we found that the chemical composition of the solar model plays a minor role in the formation and evolution of the solar magnetic cycle.